European Lepidocyrtus lignorum-group, new findings and redescritpion of Lepidocyrtus pulchellus Denis, 1926 (Collembola, Entomobryidae) - Mateos, Eduardo (Zootaxa, 2020)
Some European species of the genus Lepidocyrtus were described almost a century ago and are only known from the type locality. This is the case of the Italian species L. pulchellus Denis, 1926, whose original description is very brief and does not allow its proper identification according to the current standards of the genus taxonomy. The study of the specimens of the type series, as well as other fresh specimens collected in several Italian locations, has allowed us to redescribe the species and expand its distributional range.